తెలంగాణ - తెలుగు సాహిత్య చరిత్ర - Mudiganti Sujatha Reddy (Andhra Saraswata Parishath, 2015)
This book is all about Telangana's literature history
Telangana - Telugu Sahitya Charitra
Keywords: Telugu; తెలంగాణ - తెలుగు సాహిత్య చరిత్ర; Telangana - Telugu Sahitya Charitra; Literature; Telugu; Telugu